Cattle Health Examination in the Kemuning Nagari Piobang Women Farmer Group, Payakumbuh District - Yurni Sari Amir; Engki Zelpina; Delli Lefiana; Prima Silvia Noor; Sujatmiko; Ramond Siregar; Ulva Mohtar Lutfi; Emilda Mita Resmini (Jurnal Pengabdian Masyarakat Bestari, 2023)
The Kemuning Women Farmers Group (KWT) is a fairly active farmer group in Jorong Ampang, Nagari Piobang, Payakumbuh District, Fifty City District, West Sumatra. KWT Kemuning has group activities in agriculture and animal husbandry. In the field of animal husbandry, he is active in raising cattle which are raised in colonies. The problem found in rearing is the poor growth of the cows. This is seen from the performance of thin cows. The service activities carried out were counseling on cattle rearing patterns, cattle health checks, making complete feed fermentation based on corn plant waste and administering worm medicine. The method of service carried out is in the form of lectures, discussions and direct practice. The results obtained were complete feed fermentation based on corn plant waste liked by cows and there were indications that the cows in the group were infected with worms after a cow health examination.